Thea Stilton and the mountain of fire - Stilton, Thea.; Stilton, Thea.; Razzi, Manuela; Formaggio, Ketty; Asaro, Massimo (New York : Scholastic, 2009)
"An adventure down under! Moldy mozzarella! A flock of sheep at Nicky's family's Australian ranch was losing all its wool, and no one knew why. Nicky and her friends the Thea Sisters headed to Australia and set off on a tour of the whole country in serch of clues. What happened next turned out to be a truly memorable outback adventure!" -- P. [4] of cover.
007-010
Keywords: Stilton, Geronimo -- Juvenile fiction; Stilton, Thea -- Juvenile fiction; Mice -- Juvenile fiction; Ranches -- Australia -- Juvenile fiction; Mice -- Fiction; Adventure fiction